The The Effect of Gerga Orange Peel Extract Nanoemulsion Gel on Wound Area in Rats - Tiara Helmiza; Miftahurrahmah Miftahurrahmah; Wahyu Indah Dewi Aurora; Denok Tri Hardiningsih; Hafizah Hafizah; Anggelia Puspasari; Erny Kusdiyah (Rifa'Institute, 2026)
Introduction: Gerga orange peel contains flavonoids, tannins, saponins, vitamin C, alkaloids, and essential oils that may support wound healing through antioxidant, anti-inflammatory, and antimicrobial activity. Objective: To determine the effect of Gerga orange peel extract nanoemulsion gel on wound area changes in male Wistar rats. Method: This post-test-only controlled laboratory experiment included 24 male Wistar rats divided into six groups: negative control, 0.1% gentamicin sulfate positive control, Gerga orange peel extract gel, and Gerga orange peel extract nanoemulsion gels at 2.5%, 5%, and 7.5%. Wound area was measured on days 1, 7, and 14 using ImageJ. Data were analyzed using Kruskal-Wallis and post hoc tests. Result and Discussion: All groups showed wound area reduction. The greatest median reduction from day 1 to day 7 occurred with 2.5% nanoemulsion (93.340 mm²). The greatest reductions from day 7 to day 14 and day 1 to day 14 occurred with extract gel (149.392 mm² and 175.985 mm²). A significant between-group difference was found only from day 7 to day 14 (p = 0.010). Conclusions: Gerga orange peel extract gel and Gerga orange peel extract nanoemulsion gel reduced wound area, but the most effective nanoemulsion concentration could not be established.